Is the African Union an exact replication of the old OAU? - GHEBREMEDHIN, Daniel (KDI School, 2017)
As a continental Organization with almost half a century existence where its charters where molded to address the 1960’s issues, The Organization of African Unity (OAU) was considered to be old enough to tackle Africa’s twenty first century challenges. Consequently it was replaced with a new and restructured union, which is believed to be capable of addressing the pressing challenges facing Africa. Nevertheless this historical breakthrough raised an important question on the originality and effectiveness of the newly restructured African Union (AU). With the above mentioned arguments in view, the thesis will provide a comparative analysis of the two organizations. In order to give a clear picture on the differences and achievements of the two organizations, the paper will emphasis on the differences in charters, Organs and the principles they are created for. The three parameters which have been used by Ian hurd as the bases for measuring the effectiveness of regional and international organization namely, Effectiveness, Membership and persistence are used in this study to measure the success and effectiveness of both organizations. Moreover, major conflicts have also been discussed in this study to explore the contributions and roles played by the two organizations to settle major conflicts. It is believed to be an important parameter to measure effectiveness. Generally speaking the progress and functioning of the African Union in general and the new organs of the African union in particular in the past decade is very gradual. Nevertheless, the overall structure and the union’s mission is a real departure from the old OAU. In areas of crises and conflict resolution, the African Union still lacks the resources and enforcement mechanism as its predecessor.
Thesis(Master) --KDI School:Master of Development Policy,2017